Hypertension, pregnancy and weather: is seasonality involved? - Melo,Brena (2014)
Objective: The present study aimed at assessing the association between environmental temperature and the relative humidity of the air with frequency of hypertensive disorders of pregnancy. Methods: A prospective and retrospective, descriptive, ecological study was held at a teaching maternity in Recife, Brazil. Data from all 26.125 pregnant women admitted between 2000 and 2006 were analysed and 5.051 had the diagnosis of hypertensive disorder of pregnancy. The incidence percentages were calculated monthly per deliveries. Data on mean monthly temperature and relative humidity of the air were collected and monthly comparisons were conducted. February was chosen as the reference month due to its lowest incidence of the disease. The relative chance of hypertensive disorders of pregnancy for each other month was estimated by odds ratio and Pearson's correlation coefficient was used to calculate the relation between the incidence of hypertensive disorders of pregnancy and the mean monthly temperature and relative air humidity. Results: February presented the lowest mean monthly incidence (9.95%) and August the highest (21.54%). Pearson correlation coefficient revealed a higher incidence of hypertensive disorders of pregnancy in the cooler months (r= -0.26; p=0.046) and no significant effect of relative air humidity (r=0.20; p=0.128). Conclusion: The incidence of hypertensive disorders of pregnancy may be affected by variations in temperature, increasing during cooler periods.